INTEGRASI LITERASI KECERDASAN BUATAN DALAM PENDIDIKAN EKONOMI: EKSPLORASI KESIAPAN KOGNITIF DAN ADAPTABILITAS PEMBELAJARAN - Gayatria Oktalina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the influence of artificial intelligence (AI) literacy on cognitive readiness and learning adaptability within the context of economic education at Universitas Terbuka (Open University). A quantitative survey design was employed, involving 344 undergraduate students. The research instrument was a five-point Likert-scale questionnaire encompassing three main variables: AI literacy, cognitive readiness, and learning adaptability. Data were analyzed using SmartPLS 4.0, including validity and reliability testing, as well as path analysis to examine direct, indirect, and mediating effects among variables. The results revealed that AI literacy had a significant positive effect on both cognitive readiness (β = 0.614; p < 0.001) and learning adaptability (β = 0.318; p < 0.001). Cognitive readiness also significantly influenced learning adaptability (β = 0.467; p < 0.001). Furthermore, mediation analysis indicated that cognitive readiness partially mediated the relationship between AI literacy and learning adaptability (β = 0.287; p < 0.001). Overall, Universitas Terbuka students demonstrated high levels of AI literacy, cognitive preparedness, and adaptability to digital learning environments. These findings reinforce cognitive readiness theory and broaden the digital economic education literature by highlighting AI literacy as not merely a technical skill but a cognitive foundation for adaptive learning in the age of artificial intelligence. The study recommends integrating AI literacy into economic education curricula, developing AI-based pedagogical training for lecturers, and implementing personalized AI-assisted learning systems within open and distance universities.